Detector for tonals with harmonics - Wang, Lu (2013)
This paper presents detectors for signal with harmonics to fully explore the inherent harmonic structure of the signal with unknown fundamental frequency, amplitude and phase in complex white Gaussian noise. For signals with harmonic characteristics, a transformed power spectrum is proposed to find the energy integration of all the harmonic components. We analyze the statistical property of the transformed power spectrum and develop a harmonic tonal detector by using the method of generalized likelihood hypothesis test. Another detector which considers equal contributions of data sequences is also developed and analyzed theoretically. Both detectors fully utilize the harmonic information of the signal. Simulation results show their improvements on the detection performance.